Dilly of a death - Albert, Susan Wittig (New York : Berkley Books, 2004)
When China Bayles's formerly sensible husband, Mike McQuaid, bored with life as a teacher, takes up the new career of private detective, he and China become involved in the tangled affairs of Phoebe the Pickle Queen, owner of the largest pickle business in Texas, but things take a dangerous turn when Phoebe mysteriously vanishes just before the local Picklefest.
93162
Keywords: Bayles, China (Fictitious character); Women detectives -- Texas; Pickle industry; Herbalists; Texas; Mystery fiction